Torus Mandibularis: Etiology and Bioarcheological Utility - Brenna Hassett (Dental Anthropology Association, 2006)
Torus mandibularis is a non-metric trait commonly recorded in bioarcheological investigation and often included in the battery of non-metric traits used to analyse biological distance among populations. However, there is considerable debate regarding the etiology of the trait, with genetic and environmental factors both having been posited as the primary factor in torus development. This study of 498 individuals, drawn from eight archeological samples, investigates the variation in torus frequency in different groups as defined by sample, age, sex, and measures of functional stress. Frequencies varied significantly among both samples and dental attrition categories, supporting the idea that mandibular tori are a threshold trait, influenced by both genetic and environmental factors. Results of this study suggest the utility of mandibular tori in bioarchaeology may lie outside of biodistance analyses that rely on the high heritability quotient of non-metric traits to establish population distances.